The Role of Productivity, Household Consumption, Export, and Foreign Direct Investment In Indonesia’s GNI Improvements - Rosyadi, Thalita Maulydia; Setyo Tri Wahyudi (Contemporary Studies in Economic, Finance and Banking, 2025)
Economic growth is a key indicator of a country's successful development. Indonesia has been categorized as a middle income country for the past dozen years and is currently working to upgrade its status to a high income country. This raises the potential that Indonesia has been trapped in a middle income trap. One of the reasons why Indonesia is still a middle income country is that Indonesia has stagnated in increasing per capita income or gross national income. This study aims to analyze the middle income trap in Indonesia as one of the studies to determine the factors that affect economic growth consisting of productivity, household consumption, exports, and foreign direct investment on Indonesia's gross national income during the period 1991-2022 using the Error Correction Model (ECM) approach. The results of this study indicate that the variables of productivity, household consumption, exports, and FDI have a significant effect on Indonesia's GNI per capita in the long run. While in the short term only household consumption and export variables have a significant effect on Indonesia's GNI per capita. The results also show that Indonesia is projected to achieve high income status in 2059 by maintaining an average economic growth of at least 5%.